2D‐Korrelationsspektroskopie zur Interpretation der Entmineralisierung und Alterung deutscher Braunkohlen. Issue 10 (21st August 2014) - Schmidt, Mirjam; Otto, Matthias; Gutte, Heiner
<x xml:space="preserve">Abstract</x> Multiple methods existing for the analysis of coal all result in different values and are barely comparable. 2D correlation spectroscopy allows a higher resolution of the data as well as comparison through the application of synchronous or asynchronous algorithms. In this study, german lignite was demineralized time‐dependently as well as subjected to simulated aging, and analyzed with attenuated total reflectance infrared spectrometry. Both test series were interpreted with the help of 2D correlation spectroscopy to illustrate its potential.